Genetics and the success of East African distance runners - Scott, R. A.; Pitsiladis, Y. P. (International SportMed Journal, 2006)
A look at the medal podium in almost any international sporting competition reveals that some athletes and certain countries enjoy regular success in particular events. One of the most compelling examples is that of East African runners and their domination of international distance running competition. This phenomenon has led to the suggestion that East Africans possess some inherent genetic advantage predisposing them to superior athletic performances. The concurrent success of athletes of West African ancestry in sprint events appears to have augmented this belief given their similar skin colour. Despite the speculation that African athletes have a genetic advantage, there is no genetic evidence to dateto suggest that this is the case, although research is at an early stage. The only available genetic studies of African athletes do not find that these athletes possess a unique genetic makeup; rather they serve to highlight the high degree of genetic diversity in East Africa and also among elite East African athletes. Although genetic contributions to the phenomenal success of East Africans in distance running cannot be excluded, results to date predominantly implicate environmental factors.